Audit of state losses by the Gorontalo attorney general in a corruption case - Suardi Rais (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
In the process of proving Corruption Crime, it must fulfill the three elements contained in corruption, one of the elements of which is the loss of state finances as well as the Corruption Act. To prove the State's loss, the institutions that are authorized to audit the results of State losses will be involved. In this case the Supreme Audit Agency (BPK). As in Law No. 15 of 2006 and other institutions regulated outside the constitution, based on Circular of the Chief of the Supreme Court Number 4 of 2016, and based on the Decision of the Constitutional Court Number. 31 / PUU-X / 2012. But in some of the decisions of the Corruption Criminal Court, the process of proving the loss of state finances was carried out by the Gorontalo High Prosecutor's Office who did not have the authority to audit state financial losses in cases of corruption